2015
DOI: 10.1021/acsami.5b03378
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fragmentation of Radiation-Sensitive Novel Polymeric Resist Materials by Inner-Shell Irradiation

Abstract: Two key concepts in extreme ultraviolet lithography (EUVL) are important for it to be a candidate for the mass production of future integrated circuits: the polymer formulation and the photofragmentation process. In this work, both concepts were carefully studied. The design and synthesis of radiation-sensitive organic polymeric materials based on the inclusion of a radiation-sensitive tetrahydrothiophenium functional group are outlined. A 1-(4-methacryloyoxy)naphthalene-1-yl)tetrahydro-1H-thiophenium trifluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the last years we have studied the photofragmentation of several n-CAR homopolymers and co-polymers under EUV synchrotron radiation (SR) excitation. 4,9,15,16,21 The obtained results showed that the photodegradation processes affected mainly the triate group but also the carbon backbone of the resists. In those works it was hypothesized that the neutral sulde Ar-S-CH 3 is formed aer irradiation rendering the irradiated area insoluble in the developer.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the last years we have studied the photofragmentation of several n-CAR homopolymers and co-polymers under EUV synchrotron radiation (SR) excitation. 4,9,15,16,21 The obtained results showed that the photodegradation processes affected mainly the triate group but also the carbon backbone of the resists. In those works it was hypothesized that the neutral sulde Ar-S-CH 3 is formed aer irradiation rendering the irradiated area insoluble in the developer.…”
Section: Introductionmentioning
confidence: 91%
“…[4][5][6][7][8][9][10][11][12][13][14][15] The design paradigm has to incorporate the basic principles of conventional resists superimposed with the specic requirements of EUVL for attaining the lower nodes. 12,15,16 The interaction of the resist thin lms with high energy EUV photons (13.5 nm) is a very complex process triggered by EUV radiation that breaks the chemical bonds and simultaneously produces ablation and a high yield of secondary electrons. 15,16 This results in degassing which causes chemical and morphological changes in the resist surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of our studies, a selective bond dissociation process was observed when the excitation energy was tuned to the C 1s → π CC * transition (285.3 eV). 42 A high rate of defluorination and a loss of sulfonated groups were measured mainly at 285.3 eV of excitation energy. However, similar excitations to C 1s → π CO * or C 1s → σ C−F * did not produce important fragmentation, leading to an efficient preservation of the original chemical structures of the resists.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have studied the photochemistry and oxidation mechanisms of several resists to be used in extreme ultraviolet lithography (EUVL) for the next generation of integrated circuits. Those investigations were an attempt to understand the complex photofragmentation mechanisms after extreme ultraviolet (EUV) or inner shell excitation using SR. In one of our studies, a selective bond dissociation process was observed when the excitation energy was tuned to the C 1s → π CC * transition (285.3 eV) . A high rate of defluorination and a loss of sulfonated groups were measured mainly at 285.3 eV of excitation energy.…”
Section: Introductionmentioning
confidence: 99%